Effect of the consumption of a symbiotic shake on the intestinal microflora of erdely people - Moroti, Camila [UNESP]; Magri, Loyane Francine Souza [UNESP]; Costa, Marcela Rezende [UNESP]; Cavallini, Daniela C.U. [UNESP]; Sivieri, Katia [UNESP] (My University, 2010)
The consumption of foods containing probiotic and prebiotic ingredients is growing consistently every year, and in view of the limited number of studies investigating their effect in the elderly. Objective The objective of this study was to evaluate the effect of the consumption of a symbiotic shake containing Lactobacillus acidophilus, Bifidobacterium bifidum and fructooligosaccharides on glycemia and cholesterol levels in elderly people. Methods A randomized, double-blind, placebo-controlled study was conducted on twenty volunteers (ten for placebo group and ten for symbiotic group), aged 50 to 60 years. The criteria for inclusion in the study were: total cholesterol > 200 mg/dL; triglycerides > 200 mg/dL and glycemia > 110 mg/dL. Over a total test period of 30 days, 10 individuals (the symbiotic group) consumed a daily dose of 200 mL of a symbiotic shake containing 108 UFC/mL Lactobacillus acidophilus, 108 UFC/mL Bifidobacterium bifidum and 2 g oligofructose, while 10 other volunteers (the placebo group) drank daily the same amount of a shake that did not contain any symbiotic bacteria. Blood samples were collected 15 days prior to the start of the experiment and at 10-day intervals after the beginning of the shake intake. The standard lipid profile (total cholesterol, triglycerides and HDL cholesterol) and glycemia, or blood sugar levels, were evaluated by an enzyme colorimetric assay. Results The results of the symbiotic group showed a non-significant reduction (P > 0.05) in total cholesterol and triglycerides, a significant increase (P < 0.05) in HDL cholesterol and a significant reduction (P < 0.05) in fasting glycemia. No significant changes were observed in the placebo group. Conclusion The consumption of symbiotic shake resulted in a significant increase in HDL and a significant decrease of glycemia.
Keywords: Bifidobacterium bifidum; Fructooligosaccharide; Lactobacillus acidophilus; Symbiotics shake